Emergence of Separatist Movement in East Pakistan: Impact of Jinnah’s Leadership - Rizwan Ullah Kokab; Mahboob Hussain (Journal of Political Studies, 2017)
This paper offers a study of the impact of leadership of Quaid-i-Azam Muhammad Ali Jinnah on the Bengali Separatist Movement in its preliminary stage during the first year of the life of Pakistan when Quaid-i-Azam served as its first governor general. It would be examined whether the lingual, constitutional, economic and governmental issues, which later became a source of discontent that caused the Bengali Separatist Movement grow, were addressed by the Quaid-i-Azam Jinnah in a proper way and he did not found those mistakes which his successors in the leadership of Pakistan committed. It would also be observed that visionary leader of Quaid-i-Azam’s rank could understand the danger to the integrity of Pakistan posed by the feelings of provincialism, communism and Hindu influence in the eastern wing of Pakistan that was remote from its western part through a distance of one thousand miles. The paper will also provide a critical analysis of the steps of Quaid-i-Azam which he took for the purpose of the solidarity of newly born state of Pakistan but which steps were allegedly used as a negative propaganda against the founder of Pakistan in order to give air to the ideas of separatism in the Bengalis. In this context the Quaid’s decision for the selection of Karachi as the capital of Pakistan and his use of powers as the governor general of Pakistan would be analyzed.